2008
DOI: 10.1002/asia.200700351
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of CH2I2 and Subsequent Electron Transfer in Solution

Abstract: We studied photoinduced reactions of diiodomethane (CH(2)I(2)) upon excitation at 268 nm in acetonitrile and hexane by subpicosecond-nanosecond transient absorption spectroscopy. The transient spectra involve two absorption bands centered at around 400 (intense) and 540 nm (weak). The transients probed over the range 340-740 nm show common time profiles consisting of a fast rise (<200 fs), a fast decay ( approximately 500 fs), and a slow rise. The two fast components were independent of solute concentration, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…If this band corresponds to the 340 nm gas phase transition of CH 2 I, the absence of the stronger 280 nm transition is surprising, although the probe only extended to 290 nm and the contribution of the ground state bleach could complicate the spectrum as this lies near the peak of the CH 2 I 2 spectrum in acetonitrile (λ max ≈ 288 nm, ε max ≈ 1300 M −1 cm −1 ). 74 In the transient spectra reported here we observe a persistent UV absorption band in acetonitrile. There is an initial peak at ∼325 nm that shifts to the red, stabilizing at 356 nm within 50 ps.…”
Section: Assignment Of the Uv Absorptions In Acetonitrile And 2-bumentioning
confidence: 52%
“…If this band corresponds to the 340 nm gas phase transition of CH 2 I, the absence of the stronger 280 nm transition is surprising, although the probe only extended to 290 nm and the contribution of the ground state bleach could complicate the spectrum as this lies near the peak of the CH 2 I 2 spectrum in acetonitrile (λ max ≈ 288 nm, ε max ≈ 1300 M −1 cm −1 ). 74 In the transient spectra reported here we observe a persistent UV absorption band in acetonitrile. There is an initial peak at ∼325 nm that shifts to the red, stabilizing at 356 nm within 50 ps.…”
Section: Assignment Of the Uv Absorptions In Acetonitrile And 2-bumentioning
confidence: 52%
“…21,22 The photochemistry of dihalomethanes has also been studied in condensed phases using ultrashort laser pulses, with transient absorption measurements leading to the suggestion that the CH2I-Y isomer is formed on short timescales. [26][27][28][29][30] In contrast to the dihalomethanes, little work has been done on trihalomethanes.…”
Section: Introductionmentioning
confidence: 99%
“…Please do not adjust margins From the TA and TRR studies, it was suggested that the cold CH 2 I-I isomer is formed by the vibrational cooling of the hot CH 2 I-I isomer. [22][23][24][25][26][27][28] However, since the spectroscopic signals at the optical frequencies are not directly related to the global molecular structures at the atomic level, the structure of the hot isomer, or the precursor of the cold isomer, remains to be determined. SADS1 contains the structural information necessary for this purpose, and to shed light on the identity of the precursor of the isomer, we performed the structural fitting analysis of SADS1.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…[13][14][15][16][17] Since the formation of the isomer is rarely observed in the gas phase, [18][19][20][21] the chemical dynamics of the isomer formation has been an important topic of many experimental investigations to understand the role of the solvent cage. In this regard, diiodomethane, CH 2 I 2 , is a prototypical example and its photodissociation is known to produce a unique isomer species, isodiiodomethane (CH 2 I-I), [22][23][24][25][26][27][28][29][30][31][32][33][34] which has no analog in the gas phase ( Figure 1). 19,[35][36][37] The photodissociation dynamics of CH 2 I 2 and the formation of CH 2 I-I isomer in solution have been mainly investigated with ultrafast transient absorption (TA) spectroscopy 22-24, 38, 39 and transient resonance Raman (TRR) spectroscopy, [25][26][27][28] which successfully identified the transient spectrum assigned to the isomer and the time scale of the isomer formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation